Potensi Susu Fermentasi dalam Mempengaruhi Parameter - Furkaniaty, Annisa; Anjani, Gemala; Limijadi, Edward Kurnia Setiawan; Legowo, Anang Mohamad; Syauqy, Ahmad (Journal of Telenursing (JOTING), 2024)
This study aims to explain the effect of milk on hematological parameters. The method used is a literature review made through a systematic approach, using the PICO method, by searching for articles in the Pubmed, Scopus, and EBSCOhost databases. The research results showed that 425 articles were found, and seven articles met the inclusion criteria; these articles were fermented milk containing lactic acid bacteria, which are probiotics. Fermented milk products such as yogurt, Yakult, kefir, active, fermented goat's milk, and dahi influence hematological parameters. Namely, they can increase hemoglobin, ferritin, and erythrocyte count and reduce MCV. Milk fermentation affects hematological parameters, namely increasing hemoglobin, ferritin, and erythrocyte count and reducing MCV. Keywords: Anemia, Probiotics, Fe Absorption, Fermented Milk, Iron Status